Ethnobotanical Study of Medicinal Plants Used by Communities in Bou Village, Sojol District, Donggala Regency - Utami, Amelia Sry; Dhafir, Fatmah; Nurdin, Musdalifah; Alibasyah, Lestari M. P.; Budiarsa, I Made; Febriani, Vita Indri (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to identify and document the medicinal plant species utilized by the community in Bou Village, Sojol District, Donggala Regency, including their methods of preparation, the plant parts used, and the types of diseases treated. This research employed a qualitative descriptive design using the snowball sampling method. Data were collected through field observations, unstructured interviews with six informants who possessed traditional knowledge of medicinal plants, and direct documentation. The data were analyzed descriptively using a qualitative approach by describing the medicinal plant species identified, including their local names, scientific names, families, parts used, therapeutic uses, and methods of preparation. The results showed that 24 medicinal plant species belonging to 18 families were used to treat various ailments, most commonly fever, digestive disorders, urinary tract infections, coughs, and others. Leaves were the plant part most frequently used, while boiling was the most common method of preparation. This study highlights the importance of preserving local communities’ traditional knowledge regarding the use of medicinal plants as a form of local wisdom that has been passed down from generation to generation and should be sustainably maintained.